Resilient and sustainable destinations after disaster : challenges and strategies - Kumar, Jeetesh; Bayram, Gül Erkol; Sharma, Anukrati (Emerald Publishing Limited, 2023)
Global tourism has faced unprecedented challenges in previous years: the COVID-19 pandemic, environmental change and disaster, and financial difficulties have all contributed to rapid industry wide changes. Resilient and Sustainable Destinations After Disaster presents a multitude of perspectives into the predicaments faced by global destinations during and various crises, examining emerging trends and proposing renewed management solutions and strategies for destinations to rebuild their businesses. Structured around thematic sections, chapter authors focus on areas that include Destination Rebuilding Policy, Planning and Management, Tourism Recovery Management and The Role of Technology. The collection features an extensive range of complex issues including managing the recovery and regeneration of destinations in crisis, such as resilient destinations, crisis management and emergency response planning, post-disaster tourism, and rebuilding tourism. Resilient and Sustainable Destinations After Disaster paves the way for practitioners and academics in the hospitality and tourism sectors to find flexible and durable practises for immediate and future improvement across the industry.
Keywords: Tourism.; COVID-19 Pandemic, 2020- -- Influence.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books